"A balancing act": parents' longitudinal perspectives of weight-related discussions with their children following obesity treatment - My Sjunnestrand; Nicklas Neuman; Kajsa Järvholm; Anna Ek; Karin Nordin; Ximena Ramos Salas; Karin Eli; Paulina Nowicka (BMC, 2024)
Abstract Weight-related discussions during childhood may have long-lasting effects on children's body image and well-being. However, little is known about how parents frame these discussions with children who have undergone treatment for obesity. Our study aimed to explore how parents perceive weight-related discussions, several years after their children started obesity treatment. This qualitative study is part of the 4-year follow-up of the More and Less study, a randomized controlled trial examining the effectiveness of a parental support program as part of obesity treatment for preschool-aged children in Stockholm, Sweden. Semi-structured interviews were conducted with 33 parents (79% mothers, 48% with a university degree, 47% with foreign background) of 33 children (mean age 9.3 years (SD 0.7), 46% girls), transcribed and analyzed using realist informed thematic analysis. Three main themes, encompassing three subthemes were developed. Under the first theme, Parental attitudes and concerns, parents emphasized the importance of discussing weight and health behaviors with their children, yet found it challenging due to uncertainties about how to approach it safely and sensitively. A few parents found the conversation manageable, citing their own experiences of having overweight or their style of communication with the child as facilitating the conversation. Under the second theme, The significance of time and context, parents said they engaged in weight-related conversations with their children more frequently as the children matured, driven by their growing self-awareness. Parents also expressed how contextual factors, such as gender and the presence of others, shaped conversations. Parents perceived boys as more resilient, thus exposing them to more negative weight talk. The third theme, Navigating weight stigma, revealed how parents employed strategies such as nurturing their children's self-confidence, downplaying the significance of appearance and emphasizing health when discussing weight to shield their children from weight stigma. Taken together, we found that many parents need support to navigate weight-related discussions. Addressing weight stigma is part of children's obesity management process, as children may be bullied, teased, or experience discrimination in different social settings. More research is needed to explore how young children undergoing obesity treatment experience weight stigma and to understand gendered differences in these experiences.